Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Advances in Materials Science and Engineering, 2017)

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices. - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
In this work, polycaprolactone (PCL) was used as a basic polymer for electrospinning of random and aligned nanofiber matrices. Our aim was to develop a biocompatible substrate for ophthalmological application to improve wound closure in defects of the cornea as replacement for human amniotic membrane. We investigated whether blending the hydrophobic PCL with poly (glycerol sebacate) (PGS) or chitosan (CHI) improves the biocompatibility of the matrices for cell expansion. Human corneal epithelial cells (HCEp) and human corneal keratocytes (HCK) were used for in vitro biocompatibility studies. After optimization of the electrospinning parameters for all blends, scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and water contact angle were used to characterize the different matrices. Fluorescence staining of the F-actin cytoskeleton of the cells was performed to analyze the adherence of the cells to the different matrices. Metabolic activity of the cells was measured by cell counting kit-8 (CCK-8) for 20days to compare the biocompatibility of the materials. Our results show the feasibility of producing uniform nanofiber matrices with and without orientation for the used blends. All materials support adherence and proliferation of human corneal cell lines with oriented growth on aligned matrices. Although hydrophobicity of the materials was lowered by blending PCL, no increase in biocompatibility or proliferation, as was expected, could be measured. All tested matrices supported the expansion of human corneal cells, confirming their potential as substrates for biomedical applications.

A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.

Cultivation and characterisation of primary retinal pigment epithelium cells on nanofibre scaffolds - Heiduschka, Peter; Zimmermann, Julian Alexander; Plagemann, Tanja; Stafiej, Piotr; Himmler, Marcus; Fuchsluger, Thomas Armin; Eter, Nicole (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Identification of Process Limits for Electro-Spinning of aligned – Nano Fibres of the CPL/PGS 1: 1 blend - Bischoff, S.; Küng, Florian; Stafiej, Piotr; Fuchsluger, Thomas; Boccaccini, Aldo R.; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Influence of operating parameters on the suture retention test for scaffolds in ophthalmology - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
The strength of a suture used to attach a graft to a patient can be quantified using the suture retention test. In order to gain deeper insight on the influence of testing and application conditions testing parameters were varied. Different pull rates, suture and jaw positions, and suture materials were tested to show their influence on the result of the test. The results of the different states were analyzed using statistical tests. Based on the statistic analysis conditions for testing with a maximum of accuracy and as close as possible to in vivo conditions have been revealed.
EVALuna2:21344

Influence of the molar mass distribution on the suture-ability of nanofiber meshes for tissue engineering - Hehn, Markus; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Influence of the molecular weight on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Investigation of processing parameters for electrospun polycaprolactone / chitosan blends for wound treatment - Kümmritz, Leon; Stafiej, Piotr; Schubert, Dirk W. (15th Bayreuth Polymer Symposium, 2017)

Mapping of the electrospinning parameters for PLGA-Nanofibers - Regelmann, Christian; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Poly (glycerol sebacate)-poly (?-caprolactone) blend nanofibrous scaffold as intrinsic bio- and immunocompatible system for corneal repair - Salehi, Sahar; Czugala, Marta; Stafiej, Piotr; Fathi, Mohammadhossein; Bahners, Thomas; Gutmann, Jochen S.; Singer, Bernhard B.; Fuchsluger, Thomas (Acta Biomaterialia, 2017)
A major challenge in corneal tissue engineering and lamellar corneal transplantation is to develop synthetic scaffolds able to simulate the optical and mechanical properties of the native cornea. As a carrier, the graft scaffolds should provide the basis for anchorage, repair and regeneration. Although quite a number of scaffolds have been engineered to date, they have not been able to simultaneously recapitulate chemical, mechanical, and structural properties of the corneal extracellular matrix (ECM). Here, we examined different compositions of elastomeric biodegradable poly (glycerol sebacate) (PGS)-poly (?-caprolactone) (PCL) nanofibrous scaffolds with respect to their cyto- and immunocompatibility. These scaffolds were semi-transparent with well-defined mechanical properties and direct positive effects on viability of human corneal endothelial cells (HCEC) and human conjunctival epithelial cells (HCjEC). Moreover, within 3days HCEC established monolayers with the hexagonal morphology typical for this cell type. All PGS-PCL mixtures analyzed did not trigger effects in granulocytes, naïve and activated peripheral blood mononuclear cells (PBMCs). However, scaffolds with a higher content of PGS-PCL ratio showed the best cell organization, cyto- and immunocompatibility. Subsequently, this PGS-PCL composition could be used for further development of clinical constructs to support corneal tissue repair.In corneal tissue engineering a major challenge is the development of synthetic scaffolds with similar properties to native cornea. In our recent works, we introduced the biodegradable, polymeric nanofibrous scaffolds with similar optical and mechanical properties for corneal regeneration and here we examined the cyto- and immunocompatibility of biodegradable nanofibrous scaffolds in contact to white blood cells. Directing the alignment of human corneal cells by nanofibrous scaffolds and high viability of cells was detected by forming of endothelium monolayer with hexagonal morphology on the nanofibrous scaffold. In addition, our results for the first time show that these nanofibrous scaffolds did not trigger effects in white blood cells. These results highlight the considerable translational potential of the nanofibrous scaffolds to clinical applications.
EVALuna2:21330

Transparency and suture ability of alginate hydrogel reinforced nano-fiber scaffolds - Stafiej, Piotr; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Transparency of nanofiber reinforced alginate hydrogels for corneal wound healing - Stafiej, Piotr; Küng, Florian; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds for medical application in the eye - Stafiej, Piotr; Fuchsluger, Thomas; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds (NFHC) for medical application in ophthalmology - Stafiej, Piotr; Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien 2017, 2017)